User Needs and Factors Associated With the Acceptability of Audiovisual Feedback Devices for Chest Compression Monitoring in Cardiopulmonary Resuscitation - Kahsay, Desale Tewelde; Salanterä, Sanna; Tommila, Miretta; Liukas, Tanja; Rosio, Riitta; Diji, Abigail Kusi-Amponsah; Peltonen, Laura-Maria (Lippincott, 2025)
The use of audiovisual feedback devices to guide the quality of chest compressions during cardiopulmonary resuscitation has increased in recent years. Audiovisual feedback devices can be classified as integrated (eg, Zoll AED Plus defibrillator) or standalone (eg, CPRmeter). This study aimed to explore users' needs and factors affecting the acceptability of audiovisual feedback devices. Semistructured interviews were conducted with healthcare professionals involved in lifesaving activities. The Unified Theory of Acceptance and Use of Technology was used as a theoretical framework for the study. The Unified Theory of Acceptance and Use of Technology model has four constructs: performance expectancy, effort expectancy, social influence, and facilitating factors. Ten themes were identified under the four constructs. The performance expectancy constructs include three themes: perceived usefulness, outcome expectation, and applicability in diverse situations. The effort expectancy construct encompasses two themes: user-friendliness and complexity. The social influence construct has two themes: social and organizational factors. Lastly, the facilitating factors construct includes three themes: staff competence, perceived cost, and compatibility of devices. Exploring the needs and factors influencing the acceptability of audiovisual feedback devices used during cardiopulmonary resuscitation will inform healthcare providers, managers, manufacturers, and procurers on how to improve the efficiency and use of these devices.